The biological role of zinc in the pancreas, prostate and in submandibular glands and influence of its complex salts with chelators on the state of glands tissue - Meyramov, G.G.; Korchin, V.I.; Kohnert, K.D.; Shaybek, A.Z.; Abikenova, F.S.; Meyramova, A.G. (Fundamental and Experimental Biology, 2022)
The article provides data on the biological role of zinc in humans and animals. The main part of zinc is concentrated in three glands: Pancreas, prostate, and submandibular glands. The authors provide data on the role of zinc value and its role in each of the described glands. For the first time, zinc in the prostate and submandibular gland has been shown to interact with chelating substances, forming intra-complex salts that are well detected using histochemical methods. Analyzing data on the effect of chelators on the tissue of the prostate and submandibular glands, the authors provide data indicating that they are capable of having a damaging effect on them, causing the development of various histological changes, which serves as an indication that the damaging effect of zinc-binding complexing agents is not specific to pancreatic B cells alone; on which they have a direct damaging effect, causing their necrosis and destruction. This is also evidenced by the presented data, according to which zinc-binding chelators in the endocrine tissue of the pancreas itself have a damaging effect not only on B cells, but also on endothelial cells of blood capillaries, which is accompanied by impaired microcirculation in pancreatic islets. We provide evidence that zinc-binding substances, in particular 8-oxyquinoline derivatives, are included in some antimicrobial drugs, which need to be noted.